2008
DOI: 10.1080/14767050802361872
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor and its natural inhibitor in pre-eclampsia and SGA

Abstract: Objective Tissue factor (TF), the major activator of the extrinsic pathway of coagulation, is abundant in the placenta and decidua. The aim of this study was to determine the maternal plasma concentrations of TF and its primary inhibitor, tissue factor pathway inhibitor (TFPI), in women who delivered small for gestational age (SGA) neonates, and in preeclampsia. Study Design A cross-sectional study included the following groups: 1) women with normal pregnancies (n=86); 2) patients who delivered SGA neonates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 190 publications
7
59
0
4
Order By: Relevance
“…Moreover, the median TF concentration of patients with preeclampsia was also higher than in patients with fetal demise without hypertension. These findings are consistent with previous studies 3,53 , suggesting that elevated TF immunoreactivity and activity may be associated with the pathophysiologic process leading to preeclampsia, rather than being a consequence of the fetal death. In some of the obstetrical syndromes there was elevated tissue factor activity in the maternal circulation without a concomitant increase in the plasma concentration of this factor.…”
Section: Changes In the Hemostatic System Of Women With Obstetrical Ssupporting
confidence: 83%
See 3 more Smart Citations
“…Moreover, the median TF concentration of patients with preeclampsia was also higher than in patients with fetal demise without hypertension. These findings are consistent with previous studies 3,53 , suggesting that elevated TF immunoreactivity and activity may be associated with the pathophysiologic process leading to preeclampsia, rather than being a consequence of the fetal death. In some of the obstetrical syndromes there was elevated tissue factor activity in the maternal circulation without a concomitant increase in the plasma concentration of this factor.…”
Section: Changes In the Hemostatic System Of Women With Obstetrical Ssupporting
confidence: 83%
“…Indeed, although preterm labor was not associated with a significant change in the median maternal plasma TF concentration, the TFPI/TF ratio of these patients was lower than that of normal pregnant women, mainly due to decreased TFPI concentrations. This observation was also reported in patients with preterm PROM 77 , and those with preeclampsia 53 . The lower TFPI/TF ratio in patients with preeclampsia occurs despite the increase in the median maternal plasma TFPI concentration observed in these patients.…”
Section: Depleted or Insufficient Anticoagulant Proteins Concentrationsupporting
confidence: 50%
See 2 more Smart Citations
“…38 Although TF is required for uterine hemostasis and maintenance of the placental labyrinth during gestation, 39 increased placental TF expression can result in pregnancy complications such as preeclampsia (PE). 40,41 We previously demonstrated that pregnancy loss induced by antiphospholipid antibodies in mice is associated with increased TF expression. 16,20 In this study, we found increased TF expression and activity in placentas from CBA/J ϫ DBA/2 matings compared with control matings with normal pregnancies.…”
Section: Discussionmentioning
confidence: 99%